Can pecuniary and environmental incentives via SMS messaging make households adjust their intra-day electricity demand to a fluctuating production? - Niels Framroze Møller; Laura Mørch Andersen; Lars Gårn Hansen; Carsten Lynge Jensen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
The increasing deployment of renewables introduces substantial variability into the production of electricity, requiring demand to be more movable across time. We analyze data from a large Danish fi eld experiment (2015-2016) to investigate whether households can be prompted, via SMS messages, to move electricity consumption, and if so, whether these are motivated by pecuniary or environmental motives. To take heterogeneity fully into account we fi rst use general-to-speci c-based automatic model selection which allows for a different time-series regression for each of the 1488 households studied. From this we obtain a cross-section of estimated SMS effects which we then regress on the motive type. Since households can opt out there is a risk of self-selection. We therefore control for the size, income and average consumption of the household, and the age, educational- and labor market status of the SMS recipient. The results suggest that SMS messages can to some extent motivate households to move consumption. A stronger fi nancial motive seems more effective, whereas a purely environmental motive actually reduces the displaced amount. However, mixing financial and environmental motives seems the most effective. Finally, women and elderly people are more inclined to move consumption.
Keywords: C2; C22; C5; C55; Q4; 330; Household-level electricity demand; Automatic general-to-specific model selection; SMS messaging; field experimental data